2018
DOI: 10.3390/ijerph15112371
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis and Occupational Exposures: A Systematic Literature Review and Meta-Analyses

Abstract: Objectives: We conducted a systematic literature review to identify studies fulfilling good scientific epidemiological standards for use in meta-analyses of occupational risk factors for amyotrophic lateral sclerosis (ALS). Methods: We identified 79 original publications on associations between work and ALS. The MOOSE (Meta-analysis Of Observational Studies in Epidemiology) and GRADE (Grading of Recommendations, Assessment, Development and Evaluations) guidelines were used to ensure high scientific quality, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 107 publications
(206 reference statements)
1
33
0
1
Order By: Relevance
“…It is suggested that ALS pathogenesis might be triggered by recurrent minor or more serious electrical injuries. Although the reported evidence until now is not always supportive of the connection of ALS to electrical injury [82], current data overall tends to support this hypothesis [76,80,81].…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 68%
See 1 more Smart Citation
“…It is suggested that ALS pathogenesis might be triggered by recurrent minor or more serious electrical injuries. Although the reported evidence until now is not always supportive of the connection of ALS to electrical injury [82], current data overall tends to support this hypothesis [76,80,81].…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 68%
“…The prevalence of ALS in electricity-related occupations seems to be increased according to different epidemiological studies [76,77], case series [78] and case reports [79]. History of electric shock has been listed as one of the main risk factors that may be associated with ALS in two recent metaanalyses [80,81]. It is suggested that ALS pathogenesis might be triggered by recurrent minor or more serious electrical injuries.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…Some occupational studies give indirect evidence that workplace exposure to mercury in factories may be implicated in ALS because men with ALS tend to have occupations involving lower skills and tasks, typically associated with factory workers [46]. A recent systematic review of occupational exposures in ALS lists 15 studies in which occupational exposure to toxic metals was reported [47]. In five of these, mercury was analysed as an individual metal [48,49,50,51,52], but case and control numbers were too small in all of these reports for robust statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the involvement of many possible causal/risk factors has been suggested. This includes (but not limited to) chemicals, metals, radiation/electromagnetic fields, physical activity, dietary habits, viruses, bacteria, prions, fungi, protein-related abnormalities, mitochondria-related pathology, glutamate excitotoxicity, higher energy expenditure than intake and progressive impairment of glucose metabolism, microtubule mediated deficits in axonal transport, reactive phenotypes in astrocytes and microglia, autoimmunity, and moderate to severe traumatic brain injury [3,[6][7][8][9][10][11][12][13][14]…”
Section: Introductionmentioning
confidence: 99%